SOSIALISASI BUDAYA KESEHATAN KESELAMATAN KERJA (K3) DASAR BAGI SISWA TINGKAT SEKOLAH MENENGAH PERTAMA - Hulmansyah, Danil; Yoshandi, T. Mohd.; Syukri, Apdanil (Awal Bros Journal of Community Development, 2024)
are in a period of growth and development. The problem of occupational safety and health in schools that continues to occur is the lack of guidance regarding steps that must be taken in the school environment to prevent work accidents and work-related diseases and increase the sharpness of elementary school students in recognizing dangers that may occur. Just as accidents and illnesses caused by certain activities can be reduced or prevented as soon as possible, disasters that occur in environments such as homes, schools and roads can be prevented as soon as possible. Potential danger of accidents at home, school and on the road. The objectives of holding related to K3 are 1) getting used to behaving commendably and acting in accordance with what is right, with correct environmental management 2) increasing the ability to avoid characteristics that can endanger the environment 3) Developing sensitivity of students and the community towards environmental conditions so that Things that can harm the environment can be avoided. 4) Instill a spirit of compassion and responsibility for environmental sustainability.